Comparison of DNA probes and the Sereny test for identification of invasive Shigella and Escherichia coli strains. - Wood, P K (1986)
Forty-two Shigella and 29 Escherichia coli strains were screened for invasiveness in the Sereny test and for hybridization with two recently described DNA probes for the invasiveness plasmid. Both probes produced identical results. All Sereny-positive strains hybridized with both DNA probes. Three Sereny-negative strains also hybridized with the probes, suggesting that there are strains containing the invasiveness plasmid that are not pathogenic in animal models.